Fluorescence lifetime measurement with confocal endomicroscopy for direct analysis of tissue biochemistry in vivo. Issue 8 (August 2016) - Won, Youngjae; Park, Byungjun; Kim, Inwook; Lee, Seungrag
Abstract: Confocal endomicroscopy is a powerful tool for in vivo real-time imaging at cellular resolution inside a living body without tissue resection. Microscopic fluorescence lifetime measurement can provide information about localized biochemical conditions such as pH and the concentrations of oxygen and calcium. We hypothesized that combining these techniques could assist accurate cancer discrimination by providing both biochemical and morphological information. We designed a dual-mode experimental setup for confocal endomicroscopic imaging and fluorescence lifetime measurement and applied it to a mouse xenograft model of activated human pancreatic cancer generated by subcutaneous injection of AsPC-1 tumor cells. Using this method with pH-sensitive sodium fluorescein injection, we demonstrated discrimination between normal and cancerous tissues in a living mouse. With further development, this method may be useful for clinical cancer detection.